Biosimilar uptake by British local formularies: a cross sectional study - Alnahar, Saja; Elliott, Rachel A.; Smith, Murray D. (Springer, 2017)
Background Biological medicines are starting to lose their patent protection, so similar, inexact copies (biosimilars) are being developed and licensed. The high acquisition costs of biologics for healthcare providers could be reduced by switching to biosimilars, thus alleviating budgetary pressures and increasing patient access. Therefore, the acceptance of biosimilars by prescribers in Great Britain (GB; England, Scotland, Wales) needs to be described and understood. Objective To determine uptake of the first wave of biosimilars (somatropin, epoetin, filgrastim) by local formularies (lists of preferred medicines for prescribing in local healthcare settings). Settings This study targeted local formularies in GB. Method In November 2014, local formularies (medicines formularies of Acute Trusts and Health Boards in GB) were screened for their approach to listing of biologics and their biosimilars as well as recommendations on usage of these pharmaceuticals. Main Outcomes Measures Listing frequencies of biosimilars. Results One hundred and forty-six British local formularies were screened. Amongst the 80% of formularies in which brand names were specified, biosimilar filgrastim was the most frequently listed when compared to the other targeted biosimilars. Biosimilars were listed in preference to reference biologic medicine in 49% of local formularies for filgrastim, 11% for somatropin and in only 6% for epoetin. Conclusion Although the market for biosimilars can act in parallel to the generic market, their uptake measured using local British formularies was less than what is expected given that the British market for medicines has a strong focus on generics. Finally, geographical variability within GB requires further investigation.